Eksplorasi Layanan Konseling Kelompok dalam Mengembangkan Kreativitas Siswa: Tinjauan Literatur - Habsy, Bakhrudin All; Amali, Azzah Nabila; Salsabila, Dona Maretta; Kartikasari, Dea Dwi (Lembaga Yasin AlSys, 2024)
This research aims to find out more details about group counseling services. One of the effective guidance and counseling services for developing student creativity is group counseling services. This research uses library research methods with data originating from various sources such as books, articles, journals, documents, and others. In the discussion we explain the basic concepts of group counseling, including 1). Definition of group counseling according to expert opinion 2). Goals of Group Counseling 3). Principles of Group Counseling 4). Group Counseling Function 5). Benefits of Group Counseling 6). Group Counseling Component 7). Group Dynamics 8). Group Counseling Process and Stages.